PELATIHAN PENULISAN ARTIKEL ILMIAH DAN MANAJEMEN REFERENSI BAGI GURU SMA DI BANDAR LAMPUNG - Siti Samhati; Munaris; Muhammad Fuad; Rahmat Prayogi (Jurusan Pendidikan Bahasa dan Sastra Indonesia, FKIP Universitas Lampung, 2022)
This PKM aims to help teachers in the city of Bandar Lampung in Scientific Article Writing and Reference Management. The problems faced by partners are the lack of knowledge of writing scientific articles properly and the lack of understanding in using reference management applications. The solutions offered are the provision of material on appropriate scientific article writing strategies, and the provision of material on the use of reference management applications by Mendesly and training partners in writing articles using reference management. The method used is the explanatory method, demonstration and practice question and answer. The method of carrying out the activities is done by providing material on strategies for writing scientific articles, and providing material on reference management with tutorials on using the Mendeley application. The activity was carried out online by inviting high school teachers in Bandar Lampung City. Hasil kegiatan ini akan diseminarkan dan diterbitkan dalam jurnal Education, Language, and Arts yang terbit pada tahun 2022.